The Role of Religiosity and Work Environment Variables in Influencing Work Ethic and Turnover Intention - Istanuroaini Habibah; Musoli Musoli (Journal of Innovation, Business Management and Entrepreneurship, 2025)
The study aims to identify partially the effect of religiosity and work environment on work ethics and to identify partially the effect of religiosity, work environment and work ethic on turnover intention. This study employed quantitative data with primary data type. The research sample was medical personnel of Hospital X located in Central Java Province as many as 111 respondents. The sampling technique was purposive sampling. This study shows that partially religiosity and work environment had a significant positive effect on work ethic. Meanwhile partially religiosity, work environment and work ethic had a significant negative effect on turnover intention. Work ethics mediated the effect of religiosity on turnover intention. Work ethics mediated the effect of work environment on turnover intention.